2019
DOI: 10.3390/math7090837
|View full text |Cite
|
Sign up to set email alerts
|

Global Properties of a Delay-Distributed HIV Dynamics Model Including Impairment of B-Cell Functions

Abstract: In this paper, we construct an Human immunodeficiency virus (HIV) dynamics model with impairment of B-cell functions and the general incidence rate. We incorporate three types of infected cells, (i) latently-infected cells, which contain the virus, but do not generate HIV particles, (ii) short-lived productively-infected cells, which live for a short time and generate large numbers of HIV particles, and (iii) long-lived productively-infected cells, which live for a long time and generate small numbers of HIV p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…It is commonly observed that in viral infection processes, time delay is inevitable (see, e.g., [8][9][10][11][44][45][46][47]). Extending model (2) to include the effect of treatments and time delays will give a deeper insight into HBV infection.…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly observed that in viral infection processes, time delay is inevitable (see, e.g., [8][9][10][11][44][45][46][47]). Extending model (2) to include the effect of treatments and time delays will give a deeper insight into HBV infection.…”
Section: Resultsmentioning
confidence: 99%
“…In this section, we prove the global asymptotic stability of all equilibria by constructing Lyapunov functional following the method presented in [46][47][48][49]. Define…”
Section: Global Stability Analysismentioning
confidence: 99%
“…Mathematical modeling has been used to understand the dynamics of malaria parasites during infection and to design more effective antimalarial drugs. Malaria models were built using similar ideas to those used in virus dynamics models [8][9][10][11][12][13][14][15][16]. The basic model for the within-host dynamics of malaria infection was proposed by Anderson et al [17].…”
Section: Introductionmentioning
confidence: 99%